Critical Success Factors in Pump Production to Increase Lean Manufacturing Project Performance - Dwianditya, I Bayu; Riantini, Leni Sagita; Latief, Yusuf (UI Scholars Hub, 2024)
Floods represent a significant global disaster, occurring more frequently and causing severe damage. The effective production of pumps is crucial in supporting flood infrastructure projects. Lean Manufacturing (LM) and Project Management (PM) approaches must be incorporated to improve pump production manufacturing. Therefore, this study aims to identify the critical success factors that enhance LM performance in pump production projects for flood management through surveys conducted among pump manufacturers, governmental bodies, and relevant stakeholders engaged in flood infrastructure projects. The study's results highlight the importance of understanding and analyzing project complexity, aligning pump design with project requirements, and mastering processes and technical aspects, including method compliance and continuous improvement within the Lean framework. Effective project management, emphasizing goal clarity, planning, and execution, is also crucial. The insights obtained from this study significantly contribute to understanding the critical considerations in pump production to support flood infrastructure projects.